Defining the esports bettor: evidence from an online panel survey of emerging adults. Issue 3 (1st September 2020) - Wardle, Heather; Petrovskaya, Elena; Zendle, David
ABSTRACT: Competitive video gaming (esports) is a growing multi-national, billion-dollar industry. Esports cultures replicate traditional sports cultures, involving elite athletes, teams, league sponsorships, large viewing audiences, high profile leagues and championships, and opportunities to bet on outcomes. However, little is known about people who bet on esports, it is generally considered a niche practice. Using data from the Emerging Adults Gambling Study, a non-probability survey of 3549 people aged 16–24 living in Great Britain, the profile of esports bettors was compared with those who bet on other sports and non-gamblers. Those who bet on esports were more likely to be male, to be from nonwhite ethnic groups, to be heavily involved in playing digital games themselves, and to have higher rates of gambling involvement and problem gambling. Multivariate analysis showed a strong relationship between engaging in gambling-like practices within digital games and esports betting (for example, the purchase of loot boxes for money, or betting skins on external websites). Frequency of playing digital games was not associated with esports betting, suggesting it is not how often someone engages with digital games that is correlated with esports betting, but rather the different type of practices they undertake when playing video games.